(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2021)
The article wishes to analyze the impact of the Directive 2010/63 in the EU related to animal welfare, taking also into account the actual question about Covid-19 vaccines. The Directive aims to develop animal welfare and to harmonize states legislation in this field. For this purpose, the European Union encourages States to develop new research methods in order to replace and reduce the use of animals or, at least, to refine methods in which they should be used. Many states have correctly implemented the Directive, but some still are under the infraction procedures by the European Commission; for instance, Italy, due its more restrictive measures.